2004
DOI: 10.1093/jxb/erh124
|View full text |Cite
|
Sign up to set email alerts
|

A role for brassinosteroids in the regulation of photosynthesis in Cucumis sativus

Abstract: The effects of 24-epibrassinolide (EBR) spray application on gas-exchange, chlorophyll fluorescence characteristics, Rubisco activity, and carbohydrate metabolism were investigated in cucumber (Cucumis sativus L. cv. Jinchun No. 3) plants grown in a greenhouse. EBR significantly increased the light-saturated net CO(2) assimilation rate (A(sat)) from 3 h to 7d after spraying, with 0.1 mg l(-1) EBR proving most effective. Increased A(sat) in EBR-treated leaves was accompanied by increases in the maximum carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
182
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(216 citation statements)
references
References 40 publications
17
182
0
4
Order By: Relevance
“…Similarly, no significant changes of Fv/Fm value in wheat, grown hydroponically in EBL-containing medium [14] or foliar sprayed [34] (Shahbaz et al, 2008). Yu [12] noted that EBL significantly increased the light saturated net CO2 assimilation rate from 3 h to7 d after spraying with 0.1 mg l -1 EBL in watermelon. Increased CO2 assimilation rate in EBL treated leaves was accompanied by a higher quantum yield of PSII electron transport, mainly due to a significant increase in the photochemical quenching and unchanged efficiency of energy capture by open PSII reaction centers [12] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, no significant changes of Fv/Fm value in wheat, grown hydroponically in EBL-containing medium [14] or foliar sprayed [34] (Shahbaz et al, 2008). Yu [12] noted that EBL significantly increased the light saturated net CO2 assimilation rate from 3 h to7 d after spraying with 0.1 mg l -1 EBL in watermelon. Increased CO2 assimilation rate in EBL treated leaves was accompanied by a higher quantum yield of PSII electron transport, mainly due to a significant increase in the photochemical quenching and unchanged efficiency of energy capture by open PSII reaction centers [12] .…”
Section: Discussionmentioning
confidence: 98%
“…For example, Ali [14] reported that EBL increased growth in Indian mustard plants could be related to enhanced activity of antioxidative enzymes and proline level that protect the plants from oxidative damage. Therefore, photosynthesis which is a major controlling factor for plant growth and yield might have been increased due to EBL application [12] . In this study, foliar application of EBL enhanced CO2 assimilation rate in watermelon plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are highly effective in stimulating growth in young vegetative tissues. Brassinosteroids promoted elongation of mung bean, soybean, pea epicotyls, bean, sunflower and cucumber hypocotyls, Arabidopsis peduncles and Hordeum vulgare seedlings (Gregory, 1982;Clouse et al, 1992;Yu et al, 2004;Clouse, 2008 andKartal et al, 2009). Hypocotyl elongation of Packchoi (Brassica chinensis) by brassinosteroids was reported (Wang et al, 1993) and application to apical 3-mm region gave the best effect.…”
Section: Discussionmentioning
confidence: 99%
“…Use of BRs has also been examined in agricultural production. Several studies have established that BRs influence seed germination, plant growth, nitrogen fixation, senescence, leaf abscission and enhanced tolerance against drought and cold stress, heavy metal stress, salt stress and diseases (Khripach et al, 2000;Anuradha and Rao, 2001;Nakashita et al, 2003;Yu et al, 2004). As a consequence, extensive research has been undertaken to develop BRs as plant growth regulators for agricultural production (Ikekawa and Zhao, 1991;Sasse, 2003;Ozdimer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%